Policy Reform in a Colonial Setting: A Historical Discourse Analysis of George Stark’s Advocacy for Technical-Vocational Education - Godsend T. Chimbi; Loyiso C. Jita (E-Journal of Humanities, Arts and Social Sciences, 2023)
Colonial education is often criticized for being conservative, static, oppressive, and irrelevant to the needs and interests of the colonized people. This theoretical paper, however, disrupts the established narrative of condemnation by challenging scholars of curriculum reform to take a fresh look at colonial education policy. This study teases George Stark’s policy of technical-vocational education for Africans by employing critical policy historiography as the theoretical framework and historical discourse analysis as its methodology. Two questions drive this theoretical paper: What were the central tenets of George Stark’s curriculum reform policy in Rhodesia, and what lessons can be drawn from this policy to inform contemporary education reform in Zimbabwean secondary schools? From the research findings, it cannot be disputed that Stark’s reform policy for African education in colonial Rhodesia (now Zimbabwe) was fervently racist and discriminatory, as it was framed within the overarching scope of white hegemony. But his advocacy for a practical technical-vocational curriculum for Africans seems pragmatic, visionary, and prophetic. These findings become more compelling when considering the current clarion call for worldwide technical-vocational education. As if policy planners are scavenging nuggets from Stark’s widely condemned colonial script, the Zimbabwe government is currently piloting a reform initiative to transform secondary education from an academic to a practical-oriented curriculum. In light of these findings, it appears there are several lessons to be drawn from Stark’s colonial policy for technical-vocational education to inform current curriculum reform and practice in Zimbabwe and globally.